51.1k views
1 vote
Simplify the expression explain each step 10+(2+y)

User Hamza Ajaz
by
5.7k points

2 Answers

3 votes

Answer:

12y

Explanation:

User Eric Brandel
by
5.1k points
2 votes

The simplification of the expression 10 + (2 + y) is 12 + y.

How to simplify expressions?

10 + (2 + y)

Using PEMDAS

P = parenthesis

E = exponents

M = Multiplication

D = Division

A = Addition

S = Subtraction

So,

10 + (2 + y)

open parenthesis

= 10 + 2 + y

Add the like terms

= 12 + y

Therefore, when 10 + (2 + y) is simplified, the results is 12 + y

User ThinkingMonkey
by
5.0k points